(3Gdbhd GdeSde aj TQM fXe GdSdes - (3YHO GdQMef Hf eMeO GdUZjQ GdGNVQj, CHh RjO,J (B983 (3g` s
(3ChdgG (B:s
(3hHYO agPG JbjjO Ydi GdYde fXe YHO GdQMef GdCNVQ s
(3BNQgG (B:s
(3GdEYQGH hGdTGH eHJOC eQahY HVeI ebOQI Ydi GdjGA s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B331s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs